Teaching and Learning of English as a Foreign Language: The Impact of COVID-19 - Farooqi, Mohammad Qasim (Goodwood Publishing, 2022)
Purpose: The purpose of this study was to discover the primary changes that the higher education systems–especially at the department level–brought in their teaching systems as a result of COVID-19. Considering COVID-19, this study also explored the challenges and opportunities EFL learners experienced in their learning contexts. Research Methodology: A qualitative research design was employed in the present study where semi-structured interviews were used to collect data from the study population who were 3 teachers and 7 students sampled through the purposive sampling technique from the English Department at Badghis Institute of Higher Education in Badghis, Afghanistan. The collected data from the participants were transcribed and read several times and the emerged codes and themes were analyzed accordingly. Results: The findings of this study indicated that there were some major changes in the teaching instructions where the learners faced some barriers when trying to adapt themselves to new changes. On the other hand, the paper revealed some opportunities EFL learners experienced in dealing with the changes in the teaching and learning system. Limitations: The limited sample size and the non-random selection method could be listed as limitations of this study. Contributions: The current paper provides the readers with suggestive approaches and opportunities university teachers and students could consider during any future pandemic.